MODEL PEMBELAJARAN DARING PASCA PANDEMI COVID-19 - Sy. Rohana Sy. Rohana (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
The sophisticated information and technology (IT) development can be the answer for various problems post the covid-19 pandemic, particularly the teaching and learning challenges. The role of IT that is booming nowadays is online learning. Online learning is obviously different from regular learning. In this mode of learning, the students are required to have the ability to receive and process information. It serves as media that connect teachers and students who are being remote from one another at any time and anyplace. There are various media utilized to perform online learning such as WhatsApp, Google Meet, Zoom, Google Classroom, and other e-learning platforms. Among all these media, though, WhatsApp apparently appointed as the simplest and easiest media to access in all levels of education. Online learning at current is the effective medium to carry on the teaching and learning process in all levels of education. For the effectiveness of online teaching and learning process during the covid-19 pandemic, there have been a number of learning models suggested by the expert such as remote learning, face-to-face learning, e-learning, project-based learning, and Blended Learning.